Community Empowerment through Community Governance in the Development of Creative Markets: A Case Study of the Ndonowati Tongue Market in Surabaya City - Azizatul Kamaliyah Suwandi; Ika Devy Pramudiana; Sapto Pramono (International Journal of Social Welfare and Family Law, 2026)
This study examines the governance structure of Paguyuban Lidah Ndonowati and the development of Pasar Lidah Ndonowati as a community-based creative market in Surabaya, Indonesia, with a focus on the application of Edi Susanto’s (2005) empowerment framework. The framework, consisting of pemungkinan (enabling), penguatan (strengthening), perlindungan (protection), penyokongan (support), and pemeliharaan (maintenance), is utilized to assess how the paguyuban has contributed to the empowerment of local entrepreneurs and the sustainability of the market. The findings indicate that while the paguyuban has successfully enabled market participation, strengthened entrepreneurial capacities, and protected local interests, challenges in achieving equitable resource distribution, active participation, and adaptation to change remain. This study highlights the critical importance of collaborative governance, inclusive participation, and adaptive governance in fostering the growth of creative economies in urban communities. The research also suggests areas for improvement, particularly in addressing disparities in access to resources and ensuring long-term sustainability. The results contribute to the understanding of community-based governance as a tool for promoting economic resilience and sustainable community development. Future research should explore ways to further enhance participation and adaptability within community-based creative markets to ensure their continued success.